Clinical Outcome of Pancreatic Cancer Patients with Diabetes Mellitus: Is Diabetes a Poor Prognostic Factor? - Kang, Soonmo Peter; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Diabetes mellitus and its related factors such as hyperinsulinemia have been linked to various cancer risks and outcomes. Previous research has offered inconsistent results in terms of relationship between diabetes and pancreatic cancers. Establishing clear association between these two entities may guide us in improving clinical outcomes of pancreatic cancer patients. Two abstracts that examined the association between diabetes mellitus and pancreatic cancer are updated in this paper. Herein, the authors report updated information from the 2010 American Society of Clinical Oncology (ASCO) Annual Meeting in association between pancreatic cancer and diabetes mellitus. The present paper illustrates insufficient knowledge base to draw a conclusion in this topic. However, validation and understanding of the association could have significant clinical implications with respect to cancer prevention, early detection, and treatment. As such, further investigations are warranted to explore the link diabetes and pancreatic cancers. Image: Department of Medicine, University of Chicago. Chicago, IL, USA.